The Effectiveness Of Multimodal Approaches In Learning - Bayu Firmansyah (EDUTEC : Journal of Education And Technology, 2021)
This study aims to test the effectiveness of a multimodal approach in learning. The method used in this study is an experimental research method whose implementation uses a quasi experiment type. The steps of implementing the effectiveness test, namely (1) determining the control group and the experimental group, (2) conducting the pretest, (3) carrying out learning in the control and experimental class, (4) conducting the postest, and (5) analyzing the experimental test results. The multimodal approach has been tested through the t-test to measure its effect on improving students' literary psychological analysis skills. The results of the effectiveness test showed that there was a significant difference in the psychological analysis abilities of students in general between the post-test scores of the control class and the experimental class (p = 0.00 <0.05). This shows that the two variances are not the same, so the use of the variance to compare the population average (t-test for Equality of Means) in the t-test test must be on the basis of equal variance not assumed. At the equal variance not assumed, a t value of 8.114 was obtained and a significance level of Sig. (2-tailed) of 0.000 <0.05, p = 0.000. These results indicate that p <0.05, means that there is a significant difference between groups of students who get treatment using a multimodal approach. Thus it can be said that there is a significant difference in student learning outcomes between the experimental class with the multimodal approach compared to the control class with conventional methods. From the results of the above analysis shows that Ho is rejected, because the significance level of Sig. (2-tailed) of 0.000 <0.05, while H1 was accepted because there was a significant difference between the increase in student learning outcomes in the experimental class and the control class.